Examining the neural correlates of goal priming with the NeuroShop, a novel virtual reality fMRI paradigm. (1st March 2022) - van der Laan, L.N.; Papies, E.K.; Ly, A.; Smeets, P.A.M.
Abstract: Objective: Health goal priming has been shown to stimulate healthy food choices by activating an individual's weight-control goal. The present study combined fMRI with a novel virtual reality food choice task to elucidate the underlying neural mechanisms of health goal priming. Previous research has suggested that the ventromedial prefrontal cortex (vmPFC) and dorsolateral prefrontal cortex (dlPFC) play a role in the incorporation of health considerations into the food choice process. Responses may be more representative for those found in real life when assessed in an environment similar to the actual choice environment. Therefore, the first aim of the study was to explore if a novel virtual reality food choice task is sufficiently sensitive to detect basic valuation processes in food choice. The second aim was to examine whether increased activation in the dlPFC drives the effects of health goal priming. Methods: Fifty-six female participants performed an fMRI food choice task embedded in a virtual supermarket environment. They chose between perceived healthy and unhealthy products in a health prime, hedonic prime, and non-food control condition, while activation in brain areas involved in self-control and valuation (vmPFC, dlPFC) was assessed. Results: There were no differences in relative preference for perceived healthy products over unhealthy products between the conditions. There were also no main effects of prime condition on brain activation in the vmPFC and dPFC during food choice. Across conditions, activation in the vmPFC correlated with the tastiness of the chosen product during food choice. Conclusions: Although the study does not provide support for health goal priming triggering neural self-control mechanisms, results did show that virtual reality has potential for a more realistic fMRI food choice paradigm.